Multifunction Voltage-Mode Filter Using Single Voltage Differencing Differential Difference Amplifier - Amornchai Chaichana; Surasak Sangyaem; Winai Jaikla (My University, 2017)
In this paper, a voltage mode multifunction filter based on single voltage differencing differential difference amplifier (VDDDA) is presented. The proposed filter with three input voltages and single output voltage is constructed with single VDDDA, two capacitors and two resistors. Its quality factor can be adjusted without affecting natural frequency. Also, the natural frequency can be electronically tuned via adjusting of bias current. The filter can offer five output responses, high-pas (HP), band-pass (BP), band-reject (BR), low-pass (LP) and all-ass (AP) functions in the same circuit topology. The output response can be selected by choosing the suitable input voltage without the component matching condition and the requirement of additional double gain voltage amplifier. PSpice simulation results to confirm an operation of the proposed filter correspond to the theory.
Keywords: Analog and Mixed-Signal Circuit Design